Professional analysis of Educational Technology students with appropriate specializations - Lintang Putri Nurchalia; Yudis Ghifari; Jeremy Artistico Limbong; Linda Setiawati (Inovasi Kurikulum, 2023)
Students majoring in Educational Technology have expertise in analyzing, designing, developing, implementing, evaluating, and managing the use of technology to help solve learning problems. However, not all Educational Technology students have the same interest in choosing a specialization. Therefore This study aims to analyze the profession of educational technology students who choose specializations according to their interests and abilities. This study used a descriptive method by interviewing three educational technology students at the Indonesian University of Education. The results of the study show that educational technology students choose specializations that suit their interests and abilities. The suitability of the specialization chosen by Educational Technology students with their interests and abilities, as well as the demands of the job market in the field of education, is an important factor influencing the profession they will take after graduation. In addition, the research results also show that educational technology students who choose specializations that suit their interests and abilities tend to be more self-confident and feel more assisted in determining the profession they will pursue after graduation. The conclusion of this study is the importance of choosing a specialization that is by the interests and abilities of educational technology students in determining the profession they will pursue after graduation. AbstrakMahasiswa jurusan Teknologi Pendidikan memiliki keahlian dalam menganalisis, mendesain, mengembangkan, menerapkan, mengevaluasi, dan mengatur penggunaan teknologi untuk membantu menyelesaikan masalah pembelajaran. Namun, tidak semua mahasiswa Teknologi Pendidikan memiliki minat yang sama dalam memilih peminatan. Oleh karena itu penelitian ini bertujuan untuk menganalisis profesi mahasiswa teknologi pendidikan yang memilih peminatan pilihan sesuai dengan minat dan kemampuan mereka. Penelitian ini menggunakan metode deskriptif dengan mewawancarai kepada tiga orang mahasiswa teknologi pendidikan di Universitas Pendidikan Indonesia. Hasil penelitian menunjukkan bahwa mahasiswa teknologi pendidikan memilih peminatan pilihan yang sesuai dengan minat dan kemampuan mereka. Kesesuaian peminatan yang dipilih oleh mahasiswa Teknologi Pendidikan dengan minat dan kemampuannya serta tuntutan pasar kerja di bidang pendidikan merupakan faktor penting yang mempengaruhi profesi yang akan diambil setelah lulus. Selain itu, hasil penelitian juga menunjukkan bahwa mahasiswa teknologi pendidikan yang memilih peminatan pilihan yang sesuai dengan minat dan kemampuan mereka cenderung lebih percaya diri dan merasa lebih terbantu dalam menentukan profesi yang akan mereka tekuni setelah lulus. Kesimpulan dari penelitian ini adalah pentingnya memilih peminatan pilihan yang sesuai dengan minat dan kemampuan bagi mahasiswa teknologi pendidikan dalam menentukan profesi yang akan mereka tekuni setelah lulus.Kata Kunci: peminatan; profesi; teknologi pendidikan